Bridged Phthalocyanine Systems for Sensitization of Nanocrystalline TiO2 Films. (15th July 2010) - Zanotti, Gloria; Angelini, Nicola; Notarantonio, Sara; Paoletti, Anna Maria; Pennesi, Giovanna; Rossi, Gentilina; Lembo, Angelo; Colonna, Daniele; Di Carlo, Aldo; Reale, Andrea; Brown, Thomas M.; Calogero, Giuseppe
Abstract : Phthalocyanines based-dyes represent attractive alternatives to the expensive and polluting pyridyl based Ru complexes because of their photochemical and thermal stability, they do show in fact intense absorption in the UV/blue (Soret band) and the red/near IR (Q band) spectral regions and appear very promising as sensitizer dyes for DSSC. In this contribution we review the state of the art and the recent progress in the application of these materials as dyes for DSSC and present three new dyes which are bridged derivatives of Iron phthalocyanine. Synthesis, optical properties, electrochemical characterization and device performances are discussed with regard to the different substitution degree of the macrocycle.